2023
DOI: 10.2215/cjn.0000000000000185
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Gene Spectrum and Clinical Implication in Chinese Patients with Lupus Nephritis

Abstract: Background Lupus nephritis is a rare immunological disorder. Genetic factors are considered important in its causation. We aim to systematically investigate the rare pathogenic gene variants in patients with lupus nephritis. Methods Whole-exome sequencing was used to screen pathogenic gene variants in 1886 probands with lupus nephritis. Variants were interpreted on the basis of known pathogenic variants or the American College of Medical Genetics and Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The difference might be caused by different genetic background, time, diet and environment during the generation of mouse model. In addition, a study of IL-6-de cient BALB/C mice in pristance-induced lupus, an alternative murine lupus model, revealed that autoantibody development in this lupus model is IL-6-dependent [13]. It is true that IL-6-de ciency in MRL-Fas lpr mice reduced the level of C1q in both urine and kidney compared with MRL-Fas lpr mice in this study.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…The difference might be caused by different genetic background, time, diet and environment during the generation of mouse model. In addition, a study of IL-6-de cient BALB/C mice in pristance-induced lupus, an alternative murine lupus model, revealed that autoantibody development in this lupus model is IL-6-dependent [13]. It is true that IL-6-de ciency in MRL-Fas lpr mice reduced the level of C1q in both urine and kidney compared with MRL-Fas lpr mice in this study.…”
Section: Discussionmentioning
confidence: 46%
“…Indeed, beyond the realm of autoantibodies and immune complex deposition, a compelling body of evidence underscores the pivotal role of cytokines in the intricate tapestry of SLE pathogenesis [12] . Among these cytokines, the interleukin-6 (IL-6)/IL-6 receptor (IL-6R) signaling has garnered signi cant attention due to its robust link with LN activity in individuals with SLE [13,14] . In the context of LN, the primary source of IL-6 are the in ltrating in ammatory cells within kidneys, predominantly macrophages and monocytes [15] .…”
Section: Introductionmentioning
confidence: 99%